Interações intra- e interespecíficas e tabela de fertilidade de Cryptolaemus montrouzieri Mulsant e Tenuisvalvae notata (Mulsant) (Coleoptera: Coccinellidae) - OLIVEIRA, Cynara Moura de (2020)
The ladybeetle (Coleoptera: Coccinellidae) Tenuisvalvae notata (Mulsant), native to South America, and the Australian species Cryptolaemus montrouzieri Mulsant, are predators of mealybugs, among them Ferrisia dasylirii Cockerell (Hemiptera: Pseudococcidae). In this context, the population growth of C. montrouzieri and its spread in the Brazilian territory raises questions regarding the possible impacts on the populations of the native T. notata. Thus, the interactions of cannibalism and intraguild predation were investigated between these two species in the absence of prey. Furthermore, we estimated the fertility life table parameters of these ladybugs preying on Ferrisia dasylirii (Hemiptera: Pseudococcidae) at temperatures of 25 and 28 °C, and the number of generations in different regions in Brazil. The introduced species acted as the intraguild predator more than 80% of the time on larvae of the native species of same instar or not. Adults of C. montrouzieri preyed more on larvae and eggs of T. notata more than the contrary. Cryptolaemus montrouzieri had higher cannibalism than T. notata. For both species, development times were reduced with an increase in temperature, but female’s longevity and fecundity were not affected. Life table parameters (Ro, T e rm) were higher at 28 ˚C. The rm varied from 0.052 to 0.063 for T. notata, and from 0.048 to 0.051 for C. montrouzieri reared at 25 and 28 ˚C, respectively. It was estimated that T. notata and C. montrouzieri can complete 9 and 12 generations annually, respectively, with emphasis to Surubim-PE and Bom Jardim-PE, localities with higher temperatures, confirming the influence of temperature on the biology of the studied ladybeetle species, and potentially the biological control of mealybugs.